Una disciplina-quadro delle libertà di religione: perché, oggi più di prima, urge “provare e riprovare” a mettere al sicuro la pace religiosa (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. “Provare e riprovare” - 2. Le ragioni dell’odierna urgenza. I quattro macro fenomeni: sicurezza, crisi economica, migrazioni e populismi - 3. Di alcuni effetti dei macro fenomeni - 4. Avanzando verso la disuguaglianza graduata. Selezione degli interlocutori, margine d’apprezzamento, e limiti della “democrazia costituzionale” - 5. Le scelte di Astrid, e alcuni punti fermi - 6. Una considerazione ancora.A Framework of Freedom of Religion: for today, it urges "to try and try again" to secure religious peaceABSTRACT: This article analyzes the theme of the continuing lack of a law on religious freedom in Italy, despite the fact that seventy years have passed since the Republican Constitution was approved. According to the Author, the combination of four macro-phenomena (security, economic crisis, immigration, populism) nowadays urges the Italian Parliament to start debating how to implement the rights guaranteed under art. 19 Cost. - irrespective of the nationality of the person - and to regulate the procedures for reaching the agreements provided for in the third paragraph of art. 8 Cost. using the well-articulated bill proposed by the Astrid study group. The Author, finally, identifies a number of firm points necessary in his view to ensure respect for religious pluralism, secularism of the state and “religious peace”.
Keywords: Libertà di coscienza e di religione